2001
DOI: 10.1182/blood.v97.6.1835
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of caspase-2 long isoform in Fas-mediated cell death of human leukemic cells

Abstract: IntroductionApoptosis can be induced in many cell types by engagement of the Fas (CD95/APO-1) receptor by its natural ligand (FasL) or agonistic antibodies (anti-Fas Ab). 1,2 Fas-mediated cell death was proposed to play a role in T-cell 3 and erythroid cell 4 homeostasis. Fas receptor was also suggested to be involved in the early phase of cytotoxic drugmediated leukemic cell apoptosis. 5,6 Signaling through Fas requires its aggregation and the formation of an intracellular protein complex referred to as the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 62 publications
2
52
1
Order By: Relevance
“…From the analysis of its primary structure, caspase 2 contains a long NH 2 -terminal prodomain, which is used by apoptotic stimuli to initiate apoptosis, and an optimal recognition motif of downstream caspases to execute apoptotic processes (Harvey et al, 1997;Droin et al, 2001). To further search for the cause of the different sensitivities of LNCaP and PC3 cells to PL-induced apoptosis, the expression of caspase 2 was examined by immunoblotting ( Figure 3A).…”
Section: Caspase 2 Is Upregulated In Lncap But Not In Pc3 Cells Aftermentioning
confidence: 99%
See 2 more Smart Citations
“…From the analysis of its primary structure, caspase 2 contains a long NH 2 -terminal prodomain, which is used by apoptotic stimuli to initiate apoptosis, and an optimal recognition motif of downstream caspases to execute apoptotic processes (Harvey et al, 1997;Droin et al, 2001). To further search for the cause of the different sensitivities of LNCaP and PC3 cells to PL-induced apoptosis, the expression of caspase 2 was examined by immunoblotting ( Figure 3A).…”
Section: Caspase 2 Is Upregulated In Lncap But Not In Pc3 Cells Aftermentioning
confidence: 99%
“…Among caspase family members, caspase 2 is unique because it has features of both the long prodomain of upstream caspases and the optimal recognition motif of downstream caspases (Harvey et al, 1997;Droin et al, 2001). The prodomain is essential for the dimerisation and autoprocessing of precursor caspase 2, which allow caspase 2 to be directly activated and further initiate the caspase cascade in response to various apoptotic stimuli (Harvey et al, 1997;Droin et al, 2001).The endoplasmic reticulum (ER) is the main intracellular organelle in charge of proper folding and maturation of transmembrane and secretory proteins (Kaufman 1999;Patil and Walter, 2001;Demaurex and Distelhorst, 2003). Studies have demonstrated that the ER functions as a sensor of cellular stress to maintain homeostasis in cells Hendershot, 2001, 2004;Rutkowski and Kaufman, 2004;Schroder and Kaufman, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the activation of caspase-2 is shown to precede the processing of caspase-8 during ascididemin-induced apoptosis (Dirsch et al, 2004) or during ceramide-and etoposide-induced apoptosis (Lin et al, 2004). But in other cases, TNF␣-induced death and Fasmediated death data suggest that caspases-2 and -8 might be independently activated (Bergeron et al, 1998;Droin et al, 2001).…”
Section: Bid Is Cleaved By Caspase 8 During Tail Regressionmentioning
confidence: 99%
“…1 Several human genes encoding caspases can undergo alternative mRNA splicing, which may lead to the production of shorter proteins. 2 Caspase-2 can function as both an initiator 3 and an effector 4 caspase, depending on the death stimulus and the cell type. The 12 exon-containing CASP-2 gene has been originally described to encode two isoforms with opposite roles in apoptosis.…”
Section: Dear Editormentioning
confidence: 99%